Analisis Pendapatan Penjualan Buah dan Sayur - Mayoba May Oba; Marthen A.I Nahumury (Faculty Of Economics and Business, Musamus University, 2022)
This study aims to analyze the amount of income earned by Wamena mamas in the Wamanggu market The populatin in this study is a fruit and vegetable selling business (mama-mama wamena) in the Wamanggu market, which is 20 businesses and the sample 20 respondents. The method used is income analysis. The method consists of analysis of operating income and analysis of revenue cost ratio (R/C). The result of this study indicate that the income of the fruit and vegetable sales business (mama-mama wamena) in the wamanggu market is profitable, with an average profit for the fruit and vegetable selling business (wamena mama-mama) which is Rp. 7,956,443, per month. The results of the revenue cost retio analysis in the Wamanggu market are profitable with an average R/C value for fruit and vegetable sales (mama-mama wamena) in the Wamanggu market, which is 3. Keyword: Income, Sales, Fruit and Vegetables @